Transcriptomic Signatures of Airway Epithelium Infected With SARS-CoV-2: A Balance Between Anti-infection and Virus Load - Meng, Lingzhang; Qin, Houji; Zhao, Jingjie; He, Siyuan; Wei, Qiuju; Wang, Zechen; Shen, Jiajia; Sooranna, Suren; Song, Jian (Frontiers in Cell and Developmental Biology, 2021)
COVID-19 pneumonia requires the effective medicament and therapies. However, it is a difficult problem in drug therapy to inhibit viral replication, inhibit cytokine storm and maintain an appropriate immune response. In this study, the effects of SARS-CoV-2 on the gene expression in lung epithelial cells from patients with COVID-19 were systematically evaluated with the bioinformatic analysis methods. Transcriptome expression specific to bystander (exposed but uninfected) and infected cells was found, and the vital pathways were identified by conducting the differentially expressed gene analysis, regarding the relationship between gene signatures of COVID-19 infection and the disease severity. We found that a high viral load does not necessarily imply a low response of epithelial cells or a poor disease convalescence. Lastly, potential therapeutic drugs were predicted, and some potentially feasible COVID-19 therapeutic drugs were reported, which was expected to maintain the balance of anti-infection effect and virus load in the epithelial cells.